2005
DOI: 10.1093/hmg/ddi088
|View full text |Cite
|
Sign up to set email alerts
|

Loci for regulation of bone mineral density in men and women identified by genome wide linkage scan: the FAMOS study

Abstract: Osteoporosis is a common disease with a strong genetic component, characterized by reduced bone mass and an increased risk of fracture. Bone mineral density (BMD) is a highly heritable trait and a key determinant of osteoporotic fracture risk, but the genes responsible are incompletely defined. Here, we identified quantitative trait loci (QTL) for regulation of BMD by a genome wide scan involving 3691 individuals from 715 families, who were selected because of reduced BMD values at the lumbar spine (LS-BMD) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 36 publications
7
93
0
2
Order By: Relevance
“…The Brazilian population was composed of mixing of Europeans, Africans and native Brazilians, where an individual classified as white, according to many phenotype characteristics, presents African heredity, while another classified as black, presents . Moreover, the genes related to the BMD variation usually specifically act according to race, age and sex 21 and the BMD variation may be influenced by genetic heredity 22 . Thus, the results found in the present study suggest that the BMD stratification of Brazilian girls by race, simply considering phenotype traits, may present inaccurate results, and while studies comparing the BMD of girls and women stratified according to genetic heredity markers are not conducted, it will be impossible to understand the correlation between race and BMD in the Brazilian population.…”
Section: Physical Traitsmentioning
confidence: 99%
“…The Brazilian population was composed of mixing of Europeans, Africans and native Brazilians, where an individual classified as white, according to many phenotype characteristics, presents African heredity, while another classified as black, presents . Moreover, the genes related to the BMD variation usually specifically act according to race, age and sex 21 and the BMD variation may be influenced by genetic heredity 22 . Thus, the results found in the present study suggest that the BMD stratification of Brazilian girls by race, simply considering phenotype traits, may present inaccurate results, and while studies comparing the BMD of girls and women stratified according to genetic heredity markers are not conducted, it will be impossible to understand the correlation between race and BMD in the Brazilian population.…”
Section: Physical Traitsmentioning
confidence: 99%
“…Studies in humans have also revealed a gender difference in the degree of heritability of BMD at specific skeletal sites [24][25][26] . Ralston et al [27] provided evidence for gender-specific, site-specific and age-specific QTLs that regulate BMD in humans. However, exactly which gene is responsible for the differences observed between the males and females is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to other countries, the classification of the Brazilian population according to race using only phenotypic characteristics is difficult, mainly because of the interethnic admixed between Europeans, Africans and Amerindians, in which one individual classified as white, according to phenotypic characteristics, can have African ancestry and another classified as black can have European one 26 . There is little information about the mechanisms by which ethnicity influences BMD, but it is known that genes related to variations in BMD are race, age and gender specific 27 and that BMD is influenced by genetic ancestry 28 . In a study evaluating BMD in Afro-American women, European genetic ancestry seen in part of the sample was negatively correlated with BMD 28 .…”
Section: Discussionmentioning
confidence: 99%